Modeling the West Nile virus transfusion transmission risk in a nonoutbreak country associated with traveling donors. Issue 11 (31st August 2020) - Kiely, Philip; Seed, Clive R.; Hoad, Veronica C.; Gambhir, Manoj; Cheng, Allen C.; McQuilten, Zoe K.; Wood, Erica M.
Abstract: Background: West Nile virus (WNV) is a mosquito‐borne virus and transfusion transmission (TT) has been demonstrated. The European Union and neighboring countries experience an annual transmission season. Study Design and Methods: We developed a novel probabilistic model to estimate the WNV TT risk in Australia attributable to returned donors who had travelled to the European Union and neighboring countries during the 2018. We estimated weekly WNV TT risks in Australia for each outbreak country and the cumulative risk for all countries. Results: Highest mean weekly TT risk in Australia attributable to donors returning from a specific outbreak country was 1 in 23.3 million (plausible range, 16.8‐41.9 million) donations during Week 39 in Croatia. Highest mean weekly cumulative TT risk was 1 in 8.5 million donations (plausible range, 5.1‐17.8 million) during Week 35. Conclusions: The estimated TT risk in Australia attributable to returning donors from the European Union and neighboring countries in 2018 was very small, and additional risk mitigation strategies were not indicated. In the context of such low TT risks, a simpler but effective approach would be to monitor the number of weekly reported West Nile fever cases and implement risk modeling only when the reported cases reached a predefined number or trigger point.